UPAYA NUMBERED HEAD TOGETHER DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA SISWA MTSN 3 KOTA JAMBI - Amir Mahmud; Cunus Sa'adah (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine (1) Student learning outcomes prior to the application of Number Head Together (NHT) in mathematics lessons with set material in Class VII A MTsN 3 Jambi City. (2) Student and teacher activities when Number Head Together (NHT) is applied in mathematics lessons with set material in Class VII-A MTsN 3 Jambi City. (3) Student learning outcomes after applying Number Head Together (NHT) in Mathematics with Association Material in Class VII A MTsN 3 Jambi City. This type of research is a classroom action research conducted at MTsN 3 Jambi City in Class VII-A. The findings of this study indicate: (1) in the first cycle, an average score of 75.2 was obtained and 17 students (56.67%) had completed learning while 13 students (43.33%) had not yet achieved mastery learning. The average score of student activity reached 2.55 which indicates a sufficient category while the average score of teacher activity reached 2.6 which is categorized as sufficient (2) in the second cycle the student learning outcomes were obtained with an average score of 83.5 with complete learning reached 86.67% or as many as 26 students while 4 students (13.33%) did not achieve the completeness value of learning. The average score of student activity reached 3.55 which indicates good category while the average score of teacher activity reached 3.5 which is categorized as good.